The Analysis of Subtitling Strategies Used in Zootopia Movie - I Gusti Putu Ega Ananda Wigraha; Ida Ayu Made Puspani (RETORIKA: Jurnal Ilmu Bahasa, 2022)
Subtitling refers to the process of inserting into audio-visual media in order present the utterance which being spoken. Subtitles contain the speaker's language or English in order to be understood by the audience. It usually presented in television shows, movies or YouTube videos. This study was focused to analyze the subtitling strategies used in Zootopia Movie. The aims of the study were focused to find the types of subtitling strategies and the most frequent and least frequent subtitling strategies that can be found in the subtitles of Zootopia movie. The data source was taken from the English and Indonesian subtitles of Zootopia Movie. The data was collected through the observation method by watching and collecting the subtitles from the Zootopia Movie. A qualitative method was used in this study. The result showed that there were 10 out of 10 subtitling strategies that can be found which consist of 213 total of data such as 19 expansion (8.92%), 21 paraphrase (9.85%), 65 transfer (30.51%), 22 imitation (10.32%), 6 transcription (2.81%), 19 dislocation (8.92%), 16 condensation (7.51%), 15 decimation (7.04%), 27 deletion (12.67%) and 3 resignation (1.40%). It can be concluded that transfer was the most frequent subtitling strategy that can be found which has 65 (30.51%) data in total. On contrary, the resignation was the least frequent strategy that can be found which has 3 (1.40%) data in total.